A comprehensive evaluation method and application of shield tunnel structure health based on variable weight theory. Issue 3 (19th April 2022) - Sun, Fei; Li, Changjun
Abstract : Purpose: In order to improve the comprehensive evaluation level of shield tunnel structure health, taking a subway tunnel section as an example, and combined with the onsite measured data, such as regular inspection, health monitoring and disease remediation, this paper introduces the variable weight theory to improve the traditional fixed-weight evaluation method from structural deformation, current durability and disease status. Design/methodology/approach: Considering the influence of the fluctuation of each index value on the index weight, a comprehensive structural health evaluation model of shield tunnel based on an improved variable weight matter-element extension model is proposed. Findings: Compared with the traditional fixed-weight evaluation method, this model can correct the evaluation distortion caused by the fluctuation of index value and has optimal effect. Originality/value: The sensitive analysis shows that several key indicators of the main threats to tunnel structure are obtained to improve the efficiency of operation, maintenance and management of shield tunnel structure.